Exploration of microfluidic devices based on multi-filament threads and textiles: A review - Nilghaz, A. (AIP Publishing LLC, 2013)
In this paper, we review the recent progress in the development of low-cost microfluidic devices based on multifilament threads and textiles for semi-quantitative diagnostic and environmental assays. Hydrophilic multifilament threads are capable of transporting aqueous and non-aqueous fluids via capillary action and possess desirable properties for building fluid transport pathways in microfluidic devices. Thread can be sewn onto various support materials to form fluid transport channels without the need for the patterned hydrophobic barriers essential for paper-based microfluidic devices. Thread can also be used to manufacture fabrics which can be patterned to achieve suitable hydrophilic-hydrophobic contrast, creating hydrophilic channels which allow the control of fluids flow. Furthermore, well established textile patterning methods and combination of hydrophilic and hydrophobic threads can be applied to fabricate low-cost microfluidic devices that meet the low-cost and low-volume requirements. In this paper, we review the current limitations and shortcomings of multifilament thread and textile-based microfluidics, and the research efforts to date on the development of fluid flow control concepts and fabrication methods. We also present a summary of different methods for modelling the fluid capillary flow in microfluidic thread and textile-based systems. Finally, we summarized the published works of thread surface treatment methods and the potential of combining multifilament thread with other materials to construct devices with greater functionality. We believe these will be important research focuses of thread- and textile-based microfluidics in future.